Modern Turkish Historical Novel - Ж. Ә., Әбелдaев (Journal of Oriental Studies, 2019)
The aim of the article is to review the history of writing historical novels in modern Turkish literature. The objectives of the article are to determine the issues of national identity in historical novels, ideological and thematic features and characterization of historical figures in historical novels. Historical novel is a popular and irreplaceable type of literature. For the first time in the first quarter of the nineteenth century between the historical novel written by the English writer Walter Scott and the first Turkish historical novel there is about fifty years. Historical novels, although their popularity is growing, both from the point of view of history, and from the point of view of imagination, for a long time did not become the object of literary studies. This position remained the same apart from popular historical novels as long as works of different views were written. The innovation that began in Turkish literature with Tarik Bugra and Kemal Tahir increases the interest in historical novels, for a long time in comparison with the past, has changed the attitude of writers to history, they began to consider this issue with pride and a critical eye. The article deals with the development of historical novels in modern Turkish literature based on the works of Turkish writers. Key words: Historical novel, national identity, Turkish literature, Turkism, postmodernism, hermeneutics, Turkish prose.